INTEGRASI MODUL DIGITAL CONSENT & ETHICS SEBAGAI KURIKULUM PENDIDIKAN TINGGI: TRANSFORMASI LITERASI DIGITAL UNTUK MENANGGULANGI PELECEHAN SEKSUAL DI ERA ADAPTIF - Mirna Desy Larasati; Anggun Novita Sari; Aisyah Sayyidah Nur Hakim; Widya Gita Tantya; Ratih Rahma Nur Hidayah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The digital literacy crisis in the era of adaptation has triggered a rise in cases of online sexual harassment, which threatens mental well-being and academic integrity in higher education settings. This study aims to analyze the urgency of integrating the Digital Consent & Ethics module as a curricular transformation to address moral misconduct in cyberspace. The research method employed is qualitative, utilizing a literature review approach, which systematically examines 12 reputable international journal articles published between 2021 and 2026. The findings indicate that online sexual harassment, including image-based sexual harassment (IBSH) and image-based sexual abuse (IBSA), has become a systemic problem exacerbated by low ethical awareness and institutional failure to provide effective protection systems. The research findings emphasize that critical reading skills must be transformed into tools for self-protection and moral evaluation of digital content. This study concludes that the adoption of a Digital Consent & Ethics module encompassing cognitive, affective, and moral dimensions into higher education curricula is crucial for building a safe, inclusive, and civilized digital ecosystem in line with the Sustainable Development Goals (SDGs).